Coralligenous assemblages: research status and trends of a key Mediterranean biodiversity hotspot through bibliometric analysis - Ferrigno, Federica; Francesco Rendina; Sandulli, Roberto; Russo, Giovanni (Ecological Questions, 2023)
Coralligenous assemblages are biogenic calcareous formations endemic of the Mediterranean Sea, produced by the aggregation of calcareous red algae and other calcifying organisms in dim light conditions. Due to their high structural complexity, they are considered benthic biodiversity hotspots that provide several ecosystem functions and services. In this study, we conducted a comprehensive overview integrated with a bibliometric network analysis of the academic literature related to coralligenous assemblages. Analyses were performed using VOSviewer software. The bibliographic search on the Scopus database resulted in 339 documents published in a timeframe ranging from 1965 to 2022, with an increasing trend over time. Italy resulted the most productive country, with 202 documents and 4004 citations on this topic. The total number of authors publishing on coralligenous was 948. Piazzi was the most productive author in terms of number of documents (33), while Ballesteros was the most cited one (1109). The keyword “biodiversity” had the largest occurrence (86) and total link strength (735), highlighting the key role of these structurally-complex and heterogenic habitats. Among taxa, “algae”, “anthozoa”, and “bryozoa” were the keywords with the largest occurrence (58, 55, 31, respectively), which correspond to the main coralligenous calcifying and structuring taxa. A shift from taxonomic and ecologically-based studies, on species richness/diversity and community composition/structure, to conservation ecology ones, on anthropogenic impacts and ecosystem management, has been observed over time. These outcomes highlight the growing socio-economic awareness on the importance and vulnerability of coralligenous assemblages. Indeed, these coastal habitats have been recently recognized by the scientific and political communities for their role in providing ecosystem goods and services, although further research efforts are needed to deeply comprehend, value and protect them.